Transformational Leadership Motivation And Job Satisfaction In Kindergarten Teachers: Kepemimpinan Transformasional Motivasi Kerja Dan Kepuasan Kerja Guru TK - Masyrida Masyrida; Marwan Marwan; Munawar Munawar; Teuku Salfiyadi; Hera Yanti (Academia Open, 2026)
General Background Leadership quality in early childhood education institutions plays a strategic role in shaping organizational conditions that support teacher professionalism. Specific Background Kindergarten teachers in Aceh Tamiang District face challenges related to leadership practices, work motivation, and job satisfaction that coincide with variations in teaching performance. Knowledge Gap Empirical studies that simultaneously examine transformational leadership, work motivation, and job satisfaction within the context of early childhood education remain limited, particularly in regional kindergarten settings. Aims This study aims to examine the relationships between principals’ transformational leadership style, teachers’ work motivation, job satisfaction, and kindergarten teacher performance in Aceh Tamiang District. Results Using a quantitative survey approach with regression and path analysis, the findings indicate that transformational leadership, work motivation, and job satisfaction each show statistically significant associations with teacher performance, both individually and jointly, while also demonstrating interconnected direct and indirect pathways. Novelty This study presents a comprehensive model that integrates transformational leadership with motivational and satisfaction variables based on empirical data from kindergarten teachers in a localized educational context. Implications The results provide evidence-based considerations for school leadership practices and educational management strategies aimed at strengthening teacher performance in early childhood education settings. Highlights: Principals’ leadership practices showed measurable associations with teacher outcomes Motivational and satisfaction factors demonstrated interconnected statistical pathways Combined variables explained a substantial proportion of performance variance  Keywords: Transformational Leadership; Work Motivation; Job Satisfaction; Teacher Performance; Kindergarten Education. Published date: 2026-02-10